Development of IPM Technology for Cumin and its Evaluation in Farmer Participatory Mode - Sundria, M M; Bishnoi, H R; Rathore, B S; Rajpurohit, Abhishek (Annals of Arid Zone, 2018)
Field studies were conducted from 2006-07 to 2008-09 on development of organic plant protection modules along with IPM module in cumin (Cuminum cyminum L.) at Agricultural Research Station, Mandor, Jodhpur, and the same module were later validated during 2008-09 through farmer participatory mode at two locations of Shergath tehsil of Jodhpur district and two locations one each in Siwana and Shiv tehsils of Barmer district in arid zone of western Rajasthan. It was found that only IPM module comprising of soil treatment with Trichoderma viride (2.5 kg ha-1) + seed treatment with Trichoderma viride (6 g kg-1) + 1st spray of mancozeb (0.2%) at 30 DAS, 2nd spray of mancozeb (0.2%), acephate 75 SP (750 g ha-1) and wettable sulphur (0.2%) at 50-60 DAS and 3rd spray as repeat 2nd spray after 10-15 days of 2nd spray, reduced the per cent incidence of major diseases such as wilt, blight and powdery mildew from 7.63, 27.10 and 27.37 in unprotected treatment to 5.03, 10.47 and 14.70, respectively in IPM module. The aphid population reduced from 12.78 aphids per umbel in unprotected control to 1.27 aphids per umbel in IPM module. IPM technology was found economically viable as indicated by net return (Rs. 6844/-) and incremental cost benefit (ICB) ratio (1:3.78). Though, organic plant protection modules were effective in comparison to unprotected control but all the organic plant protection modules gave negative return and ICB ratio. Organic module comprised of soil treatment with neem cake (1.0 t ha-1) + seed treatment with Trichoderma viride (6 g kg-1 seed) + Three sprays of (Cow urine @ 10% + Neem seed kernal extract (NSKE) @ 2.5% + Garlic Extract @ 2% in equal ratio) was effective to manage wilt, blight and powdery mildew. Organic module comprising of soil treatment with tumba cake (1.5 t ha-1) + seed treatment with Trichoderma viride (6 g kg-1) + 1st spray of (cow urine @ 10%), 2nd spray of (cow urine @ 10% + Azadirachtin @ 0.03%) and 3rd spray (Karanj oil + Goshalla Keet Niyantrak @ 30 ml L-1) was most effective in controlling aphids in cumin as compared to unprotected control. Key words: Cumin, aphids, organic modules, IPM.